2022
DOI: 10.1136/jnnp-2021-328516
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of long COVID and psychiatric disorders after a hospitalisation for COVID-19: a cross-sectional study

Abstract: ObjectivesLong COVID is a major public health issue. Whether long COVID is comorbid with psychiatric disorders remains unclear. Here, we investigate the association between long COVID, psychiatric symptoms and psychiatric disorders.DesignCross-sectional.SettingsBicêtre Hospital, France, secondary care.ParticipantsOne hundred seventy-seven patients admitted in intensive care unit during acute phase and/or reporting long COVID complaints were assessed 4 months after hospitalisation for an acute COVID.Main outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
1
14
0
3
Order By: Relevance
“…Indeed, the incidence of anxiety, depression, and post-traumatic stress was 42%, 31%, and 28%, respectively, in an Italian sample [ 60 ]. Considering the alarming impact of COVID-19 on mental health, Clemente et al investigated the correlation between the psychological status of patients who had recovered from the SARS-CoV-2 infection and their inflammatory status, showing that survivors are at risk of developing psychiatric sequelae, such as anxiety, depression, and somatization symptoms, as well as sleep disorders [ 61 , 62 , 63 ]. An interesting association has also been demonstrated between high ferritin blood levels and sleep disturbances, stress, depression, and suicidal ideation [ 64 , 65 ].…”
Section: Cognitive Dysfunctions Psychiatric Symptoms and Behavioral A...mentioning
confidence: 99%
“…Indeed, the incidence of anxiety, depression, and post-traumatic stress was 42%, 31%, and 28%, respectively, in an Italian sample [ 60 ]. Considering the alarming impact of COVID-19 on mental health, Clemente et al investigated the correlation between the psychological status of patients who had recovered from the SARS-CoV-2 infection and their inflammatory status, showing that survivors are at risk of developing psychiatric sequelae, such as anxiety, depression, and somatization symptoms, as well as sleep disorders [ 61 , 62 , 63 ]. An interesting association has also been demonstrated between high ferritin blood levels and sleep disturbances, stress, depression, and suicidal ideation [ 64 , 65 ].…”
Section: Cognitive Dysfunctions Psychiatric Symptoms and Behavioral A...mentioning
confidence: 99%
“…Preventive Care in Nursing and Midwifery Journal (PCNM) 2023; 13 (1) disintegration [7]. The psychiatric complications of COVID-19 encompasses widely from depression, anxiety, panic attacks, somatic symptoms, and posttraumatic stress disorder symptoms, to delirium, psychosis and even suicidality [8][9][10][11][12]. Coupled with previous studies, there are evidences about devastating role of comorbidity in weakening the immune system, aggravating mental and physical functions and making the conditions of victims of COVID-19 more complicated [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examined possible association between long COVID, psychiatric symptoms and psychiatric disorders [ 9 ]. The authors found that the number of long COVID complaints was higher in patients with significant suicide risk.…”
mentioning
confidence: 99%
“…There are very few publications regarding the relation between long COVID and suicide [ 3 , 9 , 10 , 11 ]. This issue does not receive sufficient attention.…”
mentioning
confidence: 99%